Evaluation of Zoning System Policy Using the Discrepancy Evaluation Model at SMA Negeri 1 Jayapura - Risamasu, Putri Ellen Gracia; Sembiring, Desy Anita Karolina (Journal of Educational Learning and Innovation (ELIa), 2024)
Building the education sector is a dynamic process in line with societal changes and developments in science and technology, where openness has become a characteristic of democratic life, impacting the rapid obsolescence of government policies and educational practices. In its implementation, it is undeniable that there are still many issues in the education sector in the process of improving quality and optimizing educational equity, as this determines the quality of human resources. Various efforts have been made, one of which is through the zoning system policy in new student admissions that has been implemented since 2017. The purpose of this research is to evaluate the zoning system policy at SMA Negeri 1 Jayapura. The zoning system regulates the allocation of students to schools based on certain geographical zones. This research uses a descriptive qualitative method with semi-structured interview data collection techniques, employing the discrepancy evaluation model (DEM). The results of this study provide a deeper insight into how the zoning policy is implemented at SMA Negeri 1 Jayapura and can suggest relevant improvements based on the gaps found to enhance the effectiveness of the policy and promote improvements in the education system in the city of Jayapura.